Enhancing Security and Privacy in Blockchain Systems for Tax Administration - Mardiana; Asep Sutarman; Dyah Juliastuti; Istiqomah Yati; Lucy Patricia Pasha (IAIC Bangun Bangsa, 2025)
This research aims to analyze the implementation of blockchain technology in tax administration to improve taxpayer compliance and state revenue. The research method used involves a literature study, secondary data analysis, and interviews with experts in taxation and blockchain technology. The background of this research is the challenges faced by the government in minimizing tax non-compliance and improving the efficiency of tax administration. The main object is to evaluate the potential of blockchain as a solution to create transparency, security, and accountability in the tax system. The method used is a quantitative approach through distributing questionnaires to 11 respondents consisting of the directorate general of taxation, taxation employees, the public as service users. Results show that blockchain implementation can reduce the risk of data manipulation, increase taxpayer confidence through transparency, and support more accurate reporting and monitoring. In addition, the use of smart contracts can simplify taxation processes, such as automatic tax calculation and direct payments. The conclusion of this study confirms that blockchain has significant potential to improve tax compliance and revenue, but challenges such as implementation costs, regulations, and infrastructure readiness need to be considered. This research provides recommendations for the government to consider a phased implementation strategy with pilot projects to ensure the successful application of blockchain technology in tax administration.